The survival of direct composite restorations in the management of severe tooth wear including attrition and erosion: A prospective 8-year study. (January 2016) - Milosevic, A.; Burnside, G.
Abstract: Objectives: Survival of directly placed composite to restore worn teeth has been reported in studies with small sample sizes, short observation periods and different materials. This study aimed to estimate survival for a hybrid composite placed by one clinician up to 8-years follow-up. Methods: All patients were referred and recruited for a prospective observational cohort study. One composite was used: Spectrum ® (DentsplyDeTrey). Most restorations were placed on the maxillary anterior teeth using a Dahl approach. Results: A total of 1010 direct composites were placed in 164 patients. Mean follow-up time was 33.8 months (s.d. 27.7). 71 of 1010 restorations failed during follow-up. The estimated failure rate in the first year was 5.4% (95% CI 3.7–7.0%). Time to failure was significantly greater in older subjects ( p  = 0.005) and when a lack of posterior support was present ( p  = 0.003). Bruxism and an increase in the occlusal vertical dimension were not associated with failure. The proportion of failures was greater in patients with a Class 3 or edge-to-edge incisal relationship than in Class 1 and Class 2 cases but this was not statistically significant. More failures occurred in the lower arch (9.6%) compared to the upper arch (6%) with the largest number of composites having been placed on the maxillary incisors ( n  = 519). Conclusion: The worn dentition presents a restorative challenge but composite is an appropriate restorative material. Clinical significance: This study shows that posterior occlusal support is necessary to optimise survival.